(untitled) (Journal of Global Accounting, 2024)
The study examined the effect of debt to equity ratio on the corporate performance of listed commercial banks in Nigeria. The specific objective was to ascertain the effect of long-term debt to equity ratio and short-term debt to equity ratio on the earnings before tax margin of listed commercial banks in Nigeria. Ex-post facto research design was used in the study. From a population of thirteen (13) listed commercial banks in Nigeria, a sample size of nine (9) was obtained using purposive sampling technique. Secondary data for the study were gotten from the financial statements of the banks for a period of twelve years which spanned across 2012 to 2023. Data analyses were done in three phases: descriptive test, robustness analysis and test of hypotheses. The Panel Estimated Generalised Least Square method which was conducted for hypotheses testing revealed that: long-term debt to equity ratio has a non-significant negative effect on earnings before tax margin of listed commercial banks in Nigeria (β = -0.000967; p-value = 0.7617); short-term debt to equity ratio has a non-significant positive effect on earnings before tax margin of listed commercial banks in Nigeria (β = 0.005427; p-value = 0.5606). In conclusion, the study found that debt to equity ratio does not significantly affect the corporate performance of commercial banks in Nigeria. The study recommended that the Treasury Department in Nigerian commercial banks should however focus on maintaining an optimal debt ratio by improving equity liquidity and reducing the dependence on borrowings in order to enable the banks have more consistent profitability and reduce the risk of financial instability.